2016
DOI: 10.1016/j.clinbiochem.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitation of hexacosanoyl lysophosphatidylcholine, amino acids, acylcarnitines, and succinylacetone during FIA–ESI–MS/MS analysis of dried blood spot extracts for newborn screening

Abstract: Objectives The goal of this study was to include the quantitation of hexacosanoyl lysophosphatidylcholine, a biomarker for X-linked adrenoleukodystrophy and other peroxisomal disorders, in the routine extraction and analysis procedure used to quantitate amino acids, acylcarnitines, and succinylacetone during newborn screening. Criteria for the method included use of a single punch from a dried blood spot, one simple extraction of the punch, no high-performance liquid chromatography, and utilizing tandem mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The procedure has been slightly modified [ 14 , 15 ] to combine the existing method for acylcarnitine analysis and C26:0-lysoPC, which enables simultaneous extraction and screening for peroxisomal disorders, mitochondrial fatty acid oxidation disorders and organic acidurias. Recently, a method was developed that enables the quantification of amino acids, acylcarnitines, succinylacetone, and C26:0-lysoPC in a single dried bloodspot punch [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure has been slightly modified [ 14 , 15 ] to combine the existing method for acylcarnitine analysis and C26:0-lysoPC, which enables simultaneous extraction and screening for peroxisomal disorders, mitochondrial fatty acid oxidation disorders and organic acidurias. Recently, a method was developed that enables the quantification of amino acids, acylcarnitines, succinylacetone, and C26:0-lysoPC in a single dried bloodspot punch [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies determined plasma VLCFAs as their methyl esters followed by detection using GC or GC-MS assays [5] , [6] . Subsequently, among many species of VLCFAs, 1-hexacosanoyl-2-hydroxy- sn -glycero-3-phosphocholine (Lyso-PC 26:0) has been proposed as a sensitive biomarker for X-ALD [7] , [8] , [9] , [10] . The milestone study demonstrated that an increasing Lyso-PC 26:0 levels in the dried blood spots (DBSs) from X-ALD patients using liquid chromatography with mass spectrometric detection (LC-MS/MS) [7] .…”
Section: Introductionmentioning
confidence: 99%
“…A high-throughput liquid chromatography-tandem mass spectrometric (LC-MS/MS) method has been established to measure C26:0-lysoPC in DBS (Hubbard et al 2009) and this method has already been implemented in newborn screening programs for ALD in some countries (Vogel et al 2015). In studies on C26:0-lysoPC levels in ALD patients a limited number of ZSD patients with elevated C26:0-lysoPC levels have also been identified (Hubbard et al 2006;Haynes and De Jesús 2016), but no specific studies on C26:0-lysoPC accumulation in ZSD patients have been performed. Also, little is known about the sensitivity and specificity of this biomarker for ZSD.…”
Section: Introductionmentioning
confidence: 99%